2021
DOI: 10.1002/srin.202100364
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Estimation of Hearth Internal Geometry of an Industrial Blast Furnace

Abstract: Since the campaign of a modern blast furnace (BF) is usually restricted by its hearth integrity, monitoring the hearth internal geometry is of crucial importance for strategic operation planning. To provide an overall picture of the hearth inner geometry of a large‐scale BF in Chinese steelworks, a wear model based on the solution of an inverse heat conduction problem is developed. Using the wear model, the evolutions of erosion and skull lines in the hearth are tracked for the period from the blow‐in of the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…These studies indicated that the peripheral flow of molten iron, dissolution of molten iron, attack of zinc and alkalis, thermal stress, and fluid‐induced shear stress are the reasons for the corrosion of carbon bricks. [ 3–5 ] It was found that a certain part of the hearth refractory was eroded, the molten iron would be enriched in the inner layer of this part, and a brittle layer appeared in the outer layer of the molten iron enrichment area. [ 6–8 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies indicated that the peripheral flow of molten iron, dissolution of molten iron, attack of zinc and alkalis, thermal stress, and fluid‐induced shear stress are the reasons for the corrosion of carbon bricks. [ 3–5 ] It was found that a certain part of the hearth refractory was eroded, the molten iron would be enriched in the inner layer of this part, and a brittle layer appeared in the outer layer of the molten iron enrichment area. [ 6–8 ]…”
Section: Introductionmentioning
confidence: 99%
“…These studies indicated that the peripheral flow of molten iron, dissolution of molten iron, attack of zinc and alkalis, thermal stress, and fluid-induced shear stress are the reasons for the corrosion of carbon bricks. [3][4][5] It was found that a certain part of the hearth refractory was eroded, the molten iron would be enriched in the inner layer of this part, and a brittle layer appeared in the outer layer of the molten iron enrichment area. [6][7][8] At present, different scholars possess different views on the formation mechanism of the brittle layer, which is generally divided into the following four aspects: 1) erosion of alkali and zinc metal; 2) thermal stress; 3) infiltration of molten iron; and 4) oxidation.…”
mentioning
confidence: 99%
“…Further, it influences the internal flow field of the liquids that may affect the state (e.g., carburization) of the hot metal. Over the years, numerous efforts have been made to develop wear models that can be used to offer an overall picture of the hearth internal geometry particularly with respect to lining and skull profiles [9][10][11][12][13][14][15]. Such wear models build on the solution of inverse heat conduction problems, where the deviations between thermocouple readings and temperatures estimated by a mathematical model at the same points are minimized by iteratively altering the location and shape of the inner profile.…”
Section: Introductionmentioning
confidence: 99%
“…A generic wear model optimized for fast computation, and thus industrial application has been presented in a previous paper [11], where special emphasis was put on outlining the underlying principles of the model and introducing the measures for yielding a wellconditioned numerical problem. Some examples of the estimated lining and skull profiles featuring three-dimensional (3D) representations were also presented.…”
Section: Introductionmentioning
confidence: 99%